O reconhecimento dos saberes populares do município de São Sebastião do Paraíso – MG como patrimônio cultural imaterial - Oliveira, Lucas Cândido de (2023)
This research has as its guiding principle the Popular Culture of the interior of the state of Minas Gerais, precisely in the geographical/administrative limit corresponding to the municipality of São Sebastião do Paraíso. It involves popular knowledge of common historical subjects, collected through Oral History, which, when intertwined with historiography, gain an academic aspect, serving mainly as a source for safeguarding the Intangible Cultural Heritage, provided for in the 1988 Federal Constitution. corresponds to the year 2020, but the knowledge is fruit planted in the past, with the ancestors. The object of research contemplates the various aspects of "cure", that is, the desire of a patient to restore his health. To conquer his desire, he develops several methods enshrined in affective memory, from thanksgiving converted into popular festivals, as well as the use of knowledge, that is, he recognizes midwives, healers, pharmacists and healers, historical subjects who contribute to the cure, preservation of the city's history and memory. In view of this, the main objective of the research is to recognize this knowledge, which is part of the customs of São Sebastião do Paraíso - Minas Gerais - as Intangible Cultural Heritage, pointing to the safeguarding of representation, memory, appreciation, identity and history of these popular manifestations, through the legal tool called “Inventory”. When choosing knowledge as a source of research, there is a direct connection with the representative identities of social groups. To this end, the tool provided by Oral History is of paramount importance to carry out this work, considering that common subjects do not record their customs, which are only alive in their memories. The conductive methodology of the research is the survey of the knowledge expressed in the interviews, in the capture of private photographs which contribute to the registration of knowledge in the current legislation that conducts the preservationist guidelines and the bibliography. In total, 28 (twentyeight) interviews were collected and transcribed, related to the June festivities and knowledge, with healers, midwives, healers and pharmacists, who are extremely important for the consolidation of local history